The Influence of FOMO Leading to Purchase Intention: A Study on Culinary MSMEs in Indonesia - Kurniadi, Stefanie; Mulyana, Asep; Komaladewi, Rita (Journal of Innovation in Management, Accounting and Business, 2024)
The role of MSMEs (Micro, Small, and Medium Enterprises) in Indonesia's economy is very significant. Delving deeper into the Micro-Small category, the majority operate in the food (culinary) sector. Considering the vastness and potential of MSMEs in the culinary sector for the country's economy, it is crucial for the growth of this sector to continue. Therefore, it is very important for culinary MSME managers to understand the factors that can contribute to sustained growth in sales for culinary MSMEs. In the current era, digital media has a significant impact on increasing sales opportunities, especially TikTok, which has experienced the largest growth in Indonesia. TikTok videos have the power to create Purchase Intention. From previous research, it is evident that FOMO (Fear of Missing Out), ultimately driving consumers to want to make purchases. In recent years, the rise of social media usage has led to an increase in the phenomenon of Fear of Missing Out (FOMO) among consumers. Understanding the impact of FOMO on customer behavior has become a crucial issue for marketers seeking to effectively engage with their target audiences. This study employs a quantitative research approach, commencing with deductive reasoning derived from several hypotheses, involves 100 TikTok active users. This research is both important and urgent, as there have been no prior studies specifically examining the impact of FOMO on purchase intention within the culinary industry in Indonesia. The result will help culinary business owners and marketers increase purchase opportunities from consumers and greatly assist them in developing more effective TikTok video content.